Porokeratotic Eccrine Ostial and Dermal Duct Nevus - Mona Masoumeh Naraghi; Azita Nikoo; Azadeh Goodarzi (Hindawi Limited, 2013)
PEODDN is a rare benign cutaneous disorder that clinically resembles comedo nevus but favors the palms and soles, where pilosebaceous follicles are absent. Widespread involvement along Blaschko's lines can also occur. It is a disorder of keratinization involving the intraepidermal eccrine duct (acrosyringium) and is characterized by eccrine hamartoma and cornoid lamellation in pathology. The patient is a 29-year-old man with an 8-year history of pruritic skin lesions on his right lateral ankle. In the pathologic examination, multiple small epidermal invagination with overlying parakeratotic cornoid lamellation, loss of granular layer, and few dyskeratotic cells at the base of epidermal invagination are revealed. After clinic-pathologic correlation, the diagnosis of porokeratotic eccrine ostial and dermal duct nevus (PEODDN) was made. Late-onset and rare clinical presentation as pruritic lesion are the characteristic features that make this patient an extraordinary presentation of PEODDN.